2003
DOI: 10.1161/01.hyp.0000084372.91932.ba
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species in Endothelin-Induced Hypertension

Abstract: Abstract-Recent reports have indicated that endothelin-induced vasoconstriction in isolated aortic vascular rings may be mediated by the production of superoxide anion. The purpose of this study was to determine the role of superoxide anion in mediating the chronic renal and hypertensive actions of endothelin. Endothelin-1 (5 pmol/kg per minute) was chronically infused into the jugular vein by use of mini-osmotic pump for 9 days in male Sprague-Dawley rats and in rats treated with the superoxide anion scavenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 27 publications
7
86
1
4
Order By: Relevance
“…In support of this hypothesis, Sedeek et al recently showed that the increase in arterial pressure in response to ET-1 infusion for 9 days was attenuated by tempol. 13 Obviously, these results conflict with findings in the current study, although the reason for the difference is not clear. Sedeek et al used the same dose of ET-1; however, tempol was administered intravenously in the same minipump as with ET-1.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In support of this hypothesis, Sedeek et al recently showed that the increase in arterial pressure in response to ET-1 infusion for 9 days was attenuated by tempol. 13 Obviously, these results conflict with findings in the current study, although the reason for the difference is not clear. Sedeek et al used the same dose of ET-1; however, tempol was administered intravenously in the same minipump as with ET-1.…”
Section: Discussioncontrasting
confidence: 94%
“…9,12 In conscious rats, Sedeek et al observed that 9 days of ET-1 infusion significantly increased blood pressure that was completely abolished when rats were treated with the superoxide dismutase (SOD) mimetic, tempol. 13 In isolated carotid arteries from DOCA-salt hypertensive rats, blockade of ET A receptors and NADPH oxidase will inhibit superoxide production. 14 Furthermore, our laboratory has also shown that ET A receptor blockade can prevent the increase in blood pressure and oxidative stress in salt-sensitive ET B -deficient hypertensive rats, an example of a high-endothelin model of hypertension.…”
mentioning
confidence: 99%
“…32 In vitro studies 33 suggest that the increase in reduced nicotinamide-adenine dinucleotide phosphate oxidase activity is ET A mediated and, hence, may be increased when plasma ET-1 levels are raised. However, whether superoxide contributes significantly to BP in models of exogenous 34,35 or endogenous 32,36 elevation of ET-1 remains controversial. Our experiments confirm the results of previous transgenic studies demonstrating that an isolated increase in plasma ET-1 does not result in hypertension in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…33,35 Sedeek et al reported that the superoxide dismutase mimetic, tempol, inhibited the development of hypertension produced by infusion of ET-1 for 9 days. 36 It is important to note that Wang and Wang were unable to observe ET-1-induced hypertension in an identical preparation, ie, the same dose of ET-1 in rats on a normal salt diet. 37 The reasons for the disparate findings are not clear.…”
Section: Et-1 and Oxidative Stressmentioning
confidence: 98%
“…51 Similarly, chronic ET-1 infusion is associated with elevations in reactive oxygen species, although reports disagree as to the extent to which oxidative stress contributes to the associated hypertension. 36,52 Whereas hypertension associated with chronic ET B receptor blockade can be inhibited by ET A receptor antagonists, evidence for a role of oxidative stress, or specifically superoxide, is not straightforward. Williams et al recently observed that the superoxide dismutase mimetic, tempol, attenuated the hypertension associated with ET B receptor blockade in rats on a high-salt diet, but only during the initial days of treatment.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%